Agriculture and energy : evolving relationships and issues - Jenkins, Edgar N. (Agriculture issues and policies series., 2013)
Rising energy prices and changing energy and environmental policies have transformed the relationship between the energy and agriculture sectors. Traditionally, the relationship has been one-way, with agriculture using energy products as an input in production. During the past decade, however, the energy sector's use of agricultural products as renewable-fuel feedstocks has increased substantially. This book examines both sector and farm-level responses to changing market and policy drivers such as the increased production of biofuel crops and other sources of renewable energy, together with c.